Education on Diversity. The Contribution of Early Childhood’s Literature - Lepri, Chiara (Studi sulla Formazione/Open Journal of Education, 2019)
In recent years, in the field of publishing for the Italian children it has spread an audacious and healthy production of books aimed at early childhood capable of interpreting with intelligence, originality and care an increasingly plural and complex social reality, breaking mindsets, prejudices, cognitive canons, and leading us, through stories and images, towards recognition and appreciation of differences. Starting from some historical backgrounds, the paper intends to take a look at this editorial production to reflect on the characteristics of the best picturebooks in the perspective of education on diversity with particular reference to the theme of gender difference and homo-affectivity.